1998
DOI: 10.2165/00044011-199815010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Biotransformation of Mirtazapine in Human Volunteers

Abstract: This paper investigated the pharmacokinetics and biotransformation of mirtazapine in healthy human volunteers. The results showed that the area under the plasma drug concentration-time curve (AUC) of mirtazapine in human plasma appeared to be three times higher than the AUC of demethylmirtazapine. As mirtazapine is marketed as a racemic mixture and both enantiomers possess pharmacological properties essential for the overall activity of the racemate, the pharmacokinetics of mirtazapine were examined and appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
56
0
8

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 13 publications
9
56
0
8
Order By: Relevance
“…In human liver microsomal fractions, 8-hydroxymirtazapine, N-desmethylmirtazapine, and mirtazapine N-oxide were formed (Dahl et al, 1997). Pharmacokinetic data indicated that N-desmethylmirtazapine has activity similar to that of the parent drug; however, the activity is 5 to 10 times less than that of mirtazapine .In human studies, the R(Ϫ)-enantiomer is preferentially conjugated to form a quaternary N-glucuronide directly, but the S(ϩ)-enantiomer is preferentially transformed to 8-hydroxymirtazapine, followed by glucuronide conjugation (Delbressine et al, 1998). In the antidepressant drug mianserin, which differs from mirtazapine in that a carbon 1 Abbreviations used are: 5-HT x , postsynaptic serotonin type 1, 2, or 3; HPLC, high performance liquid chromatography; NOE, nuclear Overhauser effect; DEP, direct exposure probe; EI, electron ionization; DEP, direct exposure probe; EI, electron ionization; CD, circular dichroism.…”
mentioning
confidence: 99%
“…In human liver microsomal fractions, 8-hydroxymirtazapine, N-desmethylmirtazapine, and mirtazapine N-oxide were formed (Dahl et al, 1997). Pharmacokinetic data indicated that N-desmethylmirtazapine has activity similar to that of the parent drug; however, the activity is 5 to 10 times less than that of mirtazapine .In human studies, the R(Ϫ)-enantiomer is preferentially conjugated to form a quaternary N-glucuronide directly, but the S(ϩ)-enantiomer is preferentially transformed to 8-hydroxymirtazapine, followed by glucuronide conjugation (Delbressine et al, 1998). In the antidepressant drug mianserin, which differs from mirtazapine in that a carbon 1 Abbreviations used are: 5-HT x , postsynaptic serotonin type 1, 2, or 3; HPLC, high performance liquid chromatography; NOE, nuclear Overhauser effect; DEP, direct exposure probe; EI, electron ionization; DEP, direct exposure probe; EI, electron ionization; CD, circular dichroism.…”
mentioning
confidence: 99%
“…75,87 Demethylmirtazapine is the active metabolite, but its exposure in the human body is three times lower compared with the parent drug. 74 Low inhibitory effects of mirtazapine on major CYP isoenzymes were reported in vitro. 83,88 No significant interactions with the CYP2D6 substrates amitriptyline, clozapine, olanzapine, and risperidone were observed.…”
Section: Mirtazapinementioning
confidence: 99%
“…The most common adverse event with escitalopram was headache, and nausea with paroxetine. 74 Moreover, nausea, sweating, and obstipation were significantly less frequent compared with venlafaxine. 22,68 Cipriani et al reported better tolerability of escitalopram compared with duloxetine, paroxetine, reboxetine, sertraline, fluvoxamine, and venlafaxine.…”
mentioning
confidence: 96%
“…2). The former metabolite has no pharmacological effect, while DMR has been estimated to contribute 5-10% of the total pharmacodynamic activity of the drug (Delbressine et al, 1998). Recently, MRZ has been tested in cats (Quimby et al, 2011), dogs (Giorgi and Yun, 2011) and horses (Rouini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%